The Relationship Between Social Support And Independence Among Adolescents At The Bandung Salvation Army Orphanage - Veronica Ishabela Romaulytua Rajagukguk; Dewi Dolifah; Amanda Puspanditaning Sejati (INDOGENIUS, 2026)
Background & Objective: This study was motivated by the importance of social support as a key predictor of adolescent independence, particularly in orphanages. The aim was to empirically test the relationship between perceived social support and the level of independence among adolescents at the Bandung Salvation Army Orphanage. Method: The research employed a quantitative correlational design with a cross-sectional approach. The population included all adolescent residents, and the total sampling technique was used, yielding a sample size of 33 respondents. Data collection utilized Likert scale questionnaires, consisting of 38 items for social support and 15 items for adolescent independence. Data analysis included Univariate analysis for descriptive statistics and Bivariate analysis using the Spearman’s rho correlation test to examine the hypothesis. Result: Univariate results indicated that the majority of adolescents reported experiencing insufficient social support (Not Supporting category), with the most pronounced deficit in appraisal support. Correspondingly, the overall level of adolescent independence skewed toward the Not Independent category. The bivariate analysis confirmed a highly significant positive relationship between social support and adolescent independence, evidenced by a significance value of p<0.001. Conclusion: that social support is statistically and significantly correlated with adolescent independence in the orphanage setting. Therefore, improving the quality of social support, especially appraisal support, is essential for optimizing the development of adolescent autonomy and self-reliance.